Bank deposits and collections - Clarke, John J.; Bailey, Henry J.; Young, Robert; Joint Committee on Continuing Legal Education (U.S.) (Philadelphia, Joint Committee on Continuing Legal Education of the American Law Institute and the American Bar Association, 1972)
The fourth edition of this book present an updated discussion of the law of bank deposits and collections as codified in the provisions of Article 4 of the Uniform Commercial Code. Included also is new material that considers the impact of electronic computer directed sorting procedures on the bank collection system and possible future developments in the technology required to effect money transfers in large volume in the country.
Includes index
Includes bibliographical references.
usc 27/09/2018
Loans
Keywords: Bank deposits